A critical evaluation of the sector wide approach (SWAp) in the health sector in Zambia - Chansa, Collins (University of Cape Town, 2014)
Includes bibliographical references (leaves 113-121). === International recognition of the health problems being faced by developing countries have resulted in significant increases in external development assistance for health since the late 1980s. However, it has been established that this aid has not been effective due to poor coordination, harmonization and alignment. As part of the aid development architecture, donors and recipient countries have defined approaches, modalities and methods of working aimed at improving harmonization, alignment and management of aid for results. One such approach is the Sector Wide Approach (SWAp) which involves ensuring that "all significant funding for the sector supports a single sector policy and expenditure programme, under government leadership, adopting common approaches across the sector, and progressing towards relying on government procedures to disburse and account for all funds." (Foster et ai, 2000a, p.6).In Zambia, the health SWAp has been in existence since 1993. The adoption of the health SWAp was necessitated by a desire to optimize the use of domestic and externally mobilised financial and in-kind development assistance through the integration of all vertical programmes into a sectoral framework that would meet common national goals and objectives. This was after it was realised that the health system was inefficient in its provision of health services due to the existence of fragmented, multiple donor-assisted projects which the Ministry of Health could not effectively coordinate and manage.This paper explores the contribution of the health SWAp to the provision of effective health care in Zambia since its inception in 1993. The study considered the SWAp as both an aid instrument and as a process and the evaluation is made by looking at both the individual elements of a SWAp and the SWAp mechanism as a whole. The study assesses the contribution of the SWAp to fostering working relationships, accountability for finances and progress, efficient allocation and use of resources, financial sustainability and promotion of geographical equity of access to health care resources.The study was exploratory and a retrospective approach was used to track and associate changes before the introduction of the health SWAp and after the SWAp implementation period 1993 - 2005. In order to take account of certain contextual factors in the broad health reform continuum, a combination of qualitative and quantitative research techniques were used. This includes 21 in-depth key informant interviews, a Focus Group Discussion (FGD), non-participant observation at 4 different SWAp coordination meetings and a comprehensive document review. Study participants were senior members of the Health Sector AdviSOry Committee that were drawn from 6 provinces (including the capital city Lusaka). The actual selection of interviewees was done purposively based on the possession of requisite expertise, diversity and availability.